2015
DOI: 10.1089/brain.2013.0199
|View full text |Cite
|
Sign up to set email alerts
|

L2-Proficiency-Dependent Laterality Shift in Structural Connectivity of Brain Language Pathways

Abstract: Diffusion tensor imaging (DTI) and a longitudinal language learning approach were applied to investigate the relationship between the achieved second language (L2) proficiency during L2 learning and the reorganization of structural connectivity between core language areas. Language proficiency tests and DTI scans were obtained from German students before and after they completed an intensive 6-week course of the Dutch language. In the initial learning stage, with increasing L2 proficiency, the hemispheric domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Note that no changes are usually reported in any subcortical structures or the cerebellum in these studies. In terms of effects in the white matter, it appears that additional language training increases white matter integrity by means of decreasing its isotropic diffusivity in tracts that provide connectivity between frontal, parietal, temporal and subcortical language-related regions, and in both hemispheres (Hosoda et al, 2013;Mamiya, Richards, Coe, Eichler, Kuhl, Geschwind & Paus, 2016;Schlegel, Rudelson & Tse, 2012;Xiang, van Leeuwen, Dediu, Roberts, Norris & Hagoort, 2015). These primarily include tracts connecting frontal to temporal and/or parietal regions, both ventral tracts implicated in semantic and syntactic processing (Inferior Fronto-Occipital Fasciculus -IFOF, Inferior Longitudinal Fasciculus -ILF, Uncinate Fasciculus -UF), and dorsal tracts implicated in the processing of phonology and complex syntax (Arcuate Fasciculus -AF, Superior Longitudinal Fasciculus -SLF) (Friederici & Gierhan, 2013), but also the Corpus Callosum (CC), which is crucial for interhemispheric communication and cognitive control (Felton, Vazquez, Ramos Nuñez, Greene, Macbeth & Hernandez, 2017).…”
Section: Longitudinal Training Studies: Investigating the Trajectory mentioning
confidence: 99%
“…Note that no changes are usually reported in any subcortical structures or the cerebellum in these studies. In terms of effects in the white matter, it appears that additional language training increases white matter integrity by means of decreasing its isotropic diffusivity in tracts that provide connectivity between frontal, parietal, temporal and subcortical language-related regions, and in both hemispheres (Hosoda et al, 2013;Mamiya, Richards, Coe, Eichler, Kuhl, Geschwind & Paus, 2016;Schlegel, Rudelson & Tse, 2012;Xiang, van Leeuwen, Dediu, Roberts, Norris & Hagoort, 2015). These primarily include tracts connecting frontal to temporal and/or parietal regions, both ventral tracts implicated in semantic and syntactic processing (Inferior Fronto-Occipital Fasciculus -IFOF, Inferior Longitudinal Fasciculus -ILF, Uncinate Fasciculus -UF), and dorsal tracts implicated in the processing of phonology and complex syntax (Arcuate Fasciculus -AF, Superior Longitudinal Fasciculus -SLF) (Friederici & Gierhan, 2013), but also the Corpus Callosum (CC), which is crucial for interhemispheric communication and cognitive control (Felton, Vazquez, Ramos Nuñez, Greene, Macbeth & Hernandez, 2017).…”
Section: Longitudinal Training Studies: Investigating the Trajectory mentioning
confidence: 99%
“…It is possible that late L2 learning in particular might be considered the perfect testbed to examine the effect of neuroplastic changes as a consequence of language learning. In fact, actively learning and mastering an L2, especially later in life might involve re-training and restructuring of a number of neural structures related to L2 language production, articulation, and language comprehension, potentially leading to greater neural changes especially during the most active learning phases (Xiang et al, 2015 ). Although, neuroplasticity may decrease across the life-span (Kennedy and Raz, 2009 ) resulting in smaller detectable changes after childhood, we hypothesize that adolescent or adult L2 language learning may be a sufficiently challenging task to elicit neural changes even in the face of reduced neuroplasticity.…”
mentioning
confidence: 99%
“…Similar findings are also observed in cross-sectional studies, with its being proficiency (and to some extent, L1 background) rather than age of exposure (Hahne & Friederici, 2001;Friederici, Steinhauer & Pfeifer, 2002;Rossi, Gugler, Friederici & Hahne, 2002) that predicts more native-like P600 effects. Qualitative changes are also reported in neuroimaging studies which have observed hemispheric changes (from right to left) with increased L2 proficiency (Xiang, van Leeuwen, Dediu, Roberts, Norris & Hagoort, 2015;Xiang, Dediu, Roberts, van Oort, Norris & Hagoort, 2012). As has been argued in recent papers by formal linguists studying the acquisition of non-native language adopting neurolinguistic methodologies, the lack of age effects could be said to argue against a critical period for the acquisition of features not shared across the L1 and the L2, and fundamental difference accounts of SLA in general (Alemán Bañón et al, 2012Bañón et al, , 2014Alemán Bañón, Rothman & Miller, 2015;Bond, Gabriele, Fiorentino & Alemán Bañón, 2011;Gabriele, Fiorentino & Alemán Bañón, 2013).…”
Section: L2 Syntactic Developmentmentioning
confidence: 60%